Nodulation and growth of Cedrelinga catenaeformis Ducke in experimental stands in the Manaus region – Amazonas - Magalhães, Luis M.S.; Blum, Winfried E.H (Pesquisa Agropecuaria Brasileira, 2014)
Cedrelinga catenaeformis is a native forest legume of the Amazon with a recent reasonable commercial value for sawed wood, when obtained from exploitation of primary forests. Various authors have observed that this species shows very desirable silvicultural characteristics like good production of seeds, rapid growth and good stem form. Experimental stands in areas with red-yellow podzolic soils of different textures, showed that the growth (in terms of height) of this species, in contrast to that of others like Eucalyptus deglupta and Carapa guianensis, was not significantly poorer in soils of very low fertility than its growth on the more fertile soils of finer texture. The stands studied were 3 years old with a spacing of 3 x 3 m and 3 plots of 16 trees in each area. Exchangeable bases, organic carbon and total nitrogen of these soils were determined, as well as the dry weight of roots and nodules in trenches 3.0 x 0.4 x 0.4 m in each plot. The results showed that these soils were of low fertility, low in organic carbon, high acidity and high in saturation with aluminium. There were trends towards somewhat higher fertility in the finer textured soils as well as in the surface layers. Root growth was greater in the finer textured soils than in the sandy ones. The dry weight of nodules was higher in the more sandy soils. It is apparent from the results that C. catenaeformis could be utilized in degraded areas of very low soil fertility. Apart from the observed nodulation and mycorrhizal infection, this tree is able to grow well in these low fertility soils because its roots efficiently explore the soil.
Keywords: soil acidity; AI toxicity; N2 fixation